RC beams under blast load: Reliability and sensitivity analysis. (August 2016) - Stochino, Flavio
Abstract: The effects of blast loading on structures can be very dangerous: damages and failures are expected with serious threats to structural safety and human life. Materials stresses and strains are often pushed to the limit and the modelling of these phenomena can be very complex. In order to design blast-resistant structures it is very important to determine what are the key parameters of this problem. This paper presents a reliability and parametric analysis of the response of reinforced concrete (RC) beams under blast loads. The main aim is to highlight the key parameters of the problem in order to produce information useful for the design of reliable blast-resistant RC structures. The beam has been idealised as an equivalent SDOF system, in which strain-rate effects are accounted for. This approach is convenient from a computational point of view and it has been validated by a direct comparison with a more sophisticated finite element model and with experimental results found in literature. Then a sensitivity analysis of the parameters involved in beam response under blast load has been developed. Slenderness (which has a direct effect on stiffness) and peak load prove to be the most important parameters, but span length (which has an important influence on the mass) is also a key parameter. Other variables such as concrete strength and reinforcement ratio do not seem to have a strong correlation with the beam response. Highlights: A parametric analysis of the response of RC beams under blast loads is developed. An equivalent non-linear SDOF model is adopted considering strain-rate effects. A sensitivity analysis of the parameters involved in beam response is produced. Slenderness and peak load prove to be the most important parameters.